2019
DOI: 10.1002/joa3.12155
|View full text |Cite
|
Sign up to set email alerts
|

An unusually late dislodged atrial lead catching externalized ICD‐lead conductor. A rare cause of simultaneous atrial and ICD lead over‐sensing

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“… 2 The cause of lead dislocation in one-third of patients was inadequate fixation of sleeves. 5 Regarding the late complication of atrial lead, Kristensen and colleagues 6 reported late dislodgement of the atrial lead with active fixation 7–8 years after lead implantation, and the mechanism of dislodgement was speculated to be that the operation for replacement of the new generator caused a change in the lead traction. The present case is the first case report of extremely long-term dislocation of the atrial lead with passive fixation and detailed observation by autopsy.…”
Section: Discussionmentioning
confidence: 99%
“… 2 The cause of lead dislocation in one-third of patients was inadequate fixation of sleeves. 5 Regarding the late complication of atrial lead, Kristensen and colleagues 6 reported late dislodgement of the atrial lead with active fixation 7–8 years after lead implantation, and the mechanism of dislodgement was speculated to be that the operation for replacement of the new generator caused a change in the lead traction. The present case is the first case report of extremely long-term dislocation of the atrial lead with passive fixation and detailed observation by autopsy.…”
Section: Discussionmentioning
confidence: 99%